EMPIRE: a highly parallel semiempirical molecular orbital program: 3: Born-Oppenheimer molecular dynamics - Margraf, Johannes T.; Hennemann, Matthias; Clark, Timothy (Journal of Molecular Modeling, 2020)
Direct NDDO-based Born-Oppenheimer molecular dynamics (MD) have been implemented in the semiempirical molecular orbital program EMPIRE. Fully quantum mechanical MD simulations on unprecedented time and length scales are possible, since the calculation of self-consistent wavefunctions and gradients is performed in a massively parallel manner. MD simulations can be performed in the NVE and NVT ensembles, using either deterministic (Berendsen) or stochastic (Langevin) thermostats. Furthermore, dynamics for condensed-phase systems can be performed under periodic boundary conditions. We show three exemplary applications: the dynamics of molecular reorganization upon ionization, long timescale dynamics of an endohedral fullerene, and calculation of the vibrational spectrum of a nanoparticle consisting of more than eight hundred atoms. Graphical AbstractA snapshot from an MNDO-H simulation of NH4+@C60 at 4000 K shortly before a proton crosses the fullerene wall to give NH3@C60H+.
CRIS-Team Scopus Importer:2020-02-11
Keywords: Born-Oppenheimer molecular dynamics; EMPIRE; Massively parallel; Semiempirical MO theory